GNAS Mutation Patterns in Colorectal Cancer: Insights from a Ugandan Cohort - Richard Wismayer; Rosie Matthews; Celina Whalley; Julius Kiwanuka; Fredrick Elishama Kakembo; Steve Thorn; Henry Wabinga; Michael Odida; Ian Tomlinson (Medical Science: Recent Advances and Applications Vol. 3, 2025)
Introduction: In Uganda, the incidence of colorectal cancer (CRC) is rising, though still relatively low compared to developed countries, with a 5-year survival rate of 5.6%. Western literature shows that GNAS mutations are linked with failed treatment outcomes and a poor prognosis in CRC. The GNAS gene mutations are detected in many tumour types, as with KRAS (Kirsten rat sarcoma viral oncogene homolog) mutations. The global prevalence of the GNAS mutation in colorectal tumours varies. Study Objective: The objective of this study was to determine the prevalence of pathological GNAS gene mutations and compare them to the clinicopathological features of CRC in Ugandan patients. Methodology: The participants attending the Surgical Departments of Masaka Regional Referral Hospital, Mulago National Referral Hospital, Uganda Martyrs’ Hospital, Lusaka, and Mengo Hospital were prospectively recruited. This was a cross-sectional study in which formalin-fixed paraffin-embedded (FFPE) CRC blocks were obtained from 2008 to 2021. The histopathological diagnosis of colorectal adenocarcinoma, grade and LVI status was obtained by two consultant pathologists from the H&E slides. Data was abstracted from the medical case files for AJCC stage, topography and demographics. DNA was extracted from CRC FFPE tissue blocks, and using the Qiagen custom design panel, library preparation was completed. There were 56 genes which were represented in the custom panel. The GNAS gene was sequenced using the above library preparation and NGS sequencing. Categorical data were summarised using proportions and frequencies corresponding to the GNAS mutation status. Categorical and continuous variables were analysed using Fischer’s exact tests and chi-square tests. A p-value of \(\)0.05 was considered statistically significant. Results: There were 127 CRC participants with a mean (SD) age of 54.9(16.0) years. The male: female ratio was 1.2. Late-stage (III+IV) CRC constituted 85.8% of CRC participants. The majority were moderately differentiated CRC (75.6%) and had positive lymphovascular invasion (89.8%). The majority of tumours were in the rectum (44.8%), and 74% were left-sided colon tumours. There were 36(28.3%) colorectal tumours that were GNAS mutation positive. Out of the MSI tumours, there were 18(50%) GNAS-positive tumours and 34(37.4%) GNAS-negative tumours (p=0.192). There were 4(11.1%) GNAS-positive tumours compared to 16(17.6%) GNAS-negative tumours with stage IV disease (p=0.301). Out of the tumours that were GNAS mutation positive, 40(31.5%) were KRAS mutation negative and 4(3.1%) were KRAS mutation positive (p=0.447). Conclusions: In Uganda, the prevalence of GNAS mutations is similar to the prevalence from Japan, however, different to the prevalence reported in other countries. There was no relation between GNAS mutation and demographics, topography, grade, LVI status, stage, MSI status and K-ras mutation status in Ugandan CRC patients. This is the first study in Uganda and in East Africa which has reported on the prevalence of GNAS gene mutations in CRC patients, so further studies are required in this context.